Customer Focus in European Higher Education Systems - Ivana, Diana; Dan, Sorin; Popovici, Oana Cristina (Springer, Cham, 2019)
This article looks at the idea and practice of “customer focus” in higher education. As a global trend with origins in the business and corporate world, customer focus has come to increasingly shape public services worldwide. Influenced by business thinking, terminology, and practices, governmental organizations across policy areas have used customer focus to reform public services in order to bring them closer to the demands and expectations of their users. The paper particularly analyzes changes in customer focus understanding and its implications for the European higher education policies. The aim of the article is to contribute to a better conceptualization and policy understanding of this growing approach to higher education reform.
Keywords: higher education reform; customer focus; European Union